EVALUATION on SOLID MEDICAL WASTE MANAGEMENT IN THE DISTRICT HOSPITAL OF BANGIl PASURUAN 2014 - Dian Hasanah; Waluyo Jati; Nur Haidah (Poltekkes Kemenkes Surabaya, 2014)
Medical waste denoted solid waste products that proved to be hazardous to hospitals and maycause health problems if not managed properly. An initial survey has been conducted in Bangil districthospital in Pasuruan. Outside components. that proved to have met the requirements, several problemswere discovered such as a practice of mixing medical waste and non - medical solid wastes, wastemedical bins were found to have different shape, size and color and there were no labels, the temperaturereached by incenerator combustion chamber was only :t: 800°C and it was not equipped with gas cleaningmechanism, and no special handling of the resulted ashes. This study was aimed to evaluate themanagement of solid medical waste in Bangil Pasuruanhospital.With regard to the research method, this was .a descriptive research. This research wasconducted in March - May 2014, the collected data were subjected to descriptive type of analysis/ resultswere discussed in reference to Minister of Health decree No. 1204/Menkes/SK/X/2004 on EnvironmentalHealth Requirementsfor Hospital.Solid medical waste generated in Bangil Pasuruan hospital were derived from health careactivities, ERand other facilities that included infectious materials and sharps. The largest generation ofsolid medical wastes was on Saturdays at 214.7 kg, while the smallest production was Wednesdaysthatamounted to 118.8 kg. Evaluation of solid medical waste management resulted in a value of 64, 1 % andcategorized as poor. The smallest percentage was obtained. at the generation phase by 25 % and thehighest percentage related to storage 90 %.This study concluded that the management of solid medical waste in Bangil Pasuruan hospital didnot meet the designated requirements. As a suggestion, Bangil Pasuruan hospital needs to reform themanagement of solid medical wastes, to complete insfrastructures and job descriptions should be madeavailable in writing, all requirements should be tailored to Minister of Health Decree No.1204/Menkes/SK/X/2004 on Environmental Health Requirementsfor Hospital.